Developing a kindergarten computational thinking assessment using evidence-centered design: the case of algorithmic thinking. Issue 2 (3rd April 2021) - Clarke-Midura, Jody; Silvis, Deborah; Shumway, Jessica F.; Lee, Victor R.; Kozlowski, Joseph S.
ABSTRACT: Background and Context : There is a need for early childhood assessments of computational thinking (CT). However, there is not consensus on a guiding framework, definition, or set of proxies in which to measure CT. We are addressing this problem by using Evidence Centered Design (ECD) to develop an assessment of kindergarten-aged children's CT. Objective : To present a design case on the development of the assessment, specifically the algorithmic thinking (AT) tasks and to share validity evidence that emerged. Method : We focus on the AT sub-component of CT and present the principled assessment design process using ECD. Findings : Our operationalization of CT includes spatial reasoning as a sub-component. Pilot results showed an acceptable internal consistency reliability for the AT items and critical design decisions that contributed to validity evidence. Implications : An important contribution of this work is the inclusion of spatial reasoning in our definition of early childhood CT.